Resonant x-ray absorption of strong-field-ionized CF3Br. (25th November 2020) - Fouda, A E A; Ho, P J; Dunford, R W; Kanter, E P; Krässig, B; Young, L; Peterson, E R; Landahl, E C; Pan, L; Beck, D R; Southworth, S H
Abstract: We report on an experimental and theoretical study of strong-field laser ionization of CF3 Br followed by resonant x-ray absorption at the Br K -edge. Distinct 1s → 4p, 5p Rydberg transitions of Br q + ( q = 1–4) atomic ions are observed and identified with Hartree–Fock–Slater and relativistic configuration interaction calculations. Time-dependent density functional theory and ab initio molecular dynamics calculations were performed to simulate the dissociative ionization process and the molecular orbitals for the q = 1–4 charge states. Measurements were made with both parallel and perpendicular linear polarizations of the laser and x-rays, but dichroism was not observed, indicating negligible alignment by the laser ionization process. This result is explained by calculations on atomic Br and the molecular simulation.